2018
DOI: 10.1111/acer.13841
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial with Combined Transcranial Direct Current Stimulation and Attentional Bias Modification in Alcohol‐Dependent Patients

Abstract: BackgroundModifying attentional processes with attentional bias modification (ABM) might be a relevant add‐on to treatment in addiction. This study investigated whether influencing cortical plasticity with transcranial direct current stimulation (tDCS) could increase training effects. tDCS could also help alcohol‐dependent patients to overcome craving and reduce relapse, independent of training. These approaches were combined to investigate effects in the treatment of alcoholism.MethodsNinety‐eight patients (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…Research investigating the effects of VPT-AtBM has reported changes in VPT-AtB in the expected direction in young adult drinkers (38), heavy social drinkers (35), heavy drinkers (HD) (10,32,40), and AUD (31). Another study in AUD showed a trend (27), while two studies in AUD (29,30), and one in binge drinkers (36) found no effects. It is also noteworthy that in Rinck et al (27), neither baseline bias nor bias change did mediate drinking changes.…”
Section: Atbm: Effects On Experimental Tasksmentioning
confidence: 98%
See 1 more Smart Citation
“…Research investigating the effects of VPT-AtBM has reported changes in VPT-AtB in the expected direction in young adult drinkers (38), heavy social drinkers (35), heavy drinkers (HD) (10,32,40), and AUD (31). Another study in AUD showed a trend (27), while two studies in AUD (29,30), and one in binge drinkers (36) found no effects. It is also noteworthy that in Rinck et al (27), neither baseline bias nor bias change did mediate drinking changes.…”
Section: Atbm: Effects On Experimental Tasksmentioning
confidence: 98%
“…Generally, motivation to change is assumed to be higher in populations with more problematic drinking patterns. When considering clinical trials on AtBM in AUD, however, two of four studies reported that AtBM increases the time to first drink at 3-month follow-up (31) or reduces relapse rates at 1-year follow up (27), while two other studies failed to report such effects at 4-week (29) or 1-year follow-up (30). Interestingly, those studies, which reported evidence for a bias change (27,31) were also those reporting drinking effects, while the studies, in which the bias could not be changed did not find any effects on drinking behavior (29,30).…”
Section: Atbm: Effects On Experimental Tasksmentioning
confidence: 99%
“…No significant effects for craving were found. In another study, the same group [56] (n = 83) did not find significant effects of tDCS on craving or 1-year relapse rates.…”
Section: Review Of Tdcs For Audmentioning
confidence: 87%
“…In considering context during stimulation, an interesting pattern emerges. Studies that involved the presentation of alcohol-related cues in various tasks during stimulation [51,[54][55][56]59] provide weak or no evidence of a positive effect of tDCS on alcohol-related outcomes. This is especially of interest in connection with a tDCS study done for methamphetamine use which found that tDCS reduced craving whereas stimulation was administered at rest (i.e., as monotherapy), but observed increased craving when administered during a cue-induced craving task [66].…”
Section: Review Of Tdcs For Audmentioning
confidence: 99%
“…Preliminary evidence in the field of AD have also been reported. Specifically, in a recent trial in patients with alcohol use disorders (AUD), 4 sessions of attentional bias training (control or real) were combined with either sham or active tDCS over the DLPFC, using a 2-by-2 doubleblind factorial design (den Uyl et al, 2018). Combined active tDCS and real training did not produce any significant effect on alcohol craving and relapse, and on attentional biases toward alcohol.…”
Section: Combining Cognitive Training/therapy With Nibsmentioning
confidence: 99%